Waẓīfa Sanad Network of Pesantren Al-Fithrah Surabaya with Ba'alawi Sufi Figures - Muhammad Kudhori; Ainul Yaqin; Mochamad Abduloh (Teosofia: Indonesian Journal of Islamic Mysticism, 2025)
Pesantren Al-Fithrah Surabaya, established by KH. Ahmad Asrori al-Ishaqi functions not only as an educational center but also as a hub for the Tariqa Qadiriyya wa Naqshbandiyya al-Utsmaniyyah (TQN al-‘Utsmaniyyah). Waẓīfa, spiritual practices, rooted in Sufi Ba’alawi tradition, have become a necessity for students in this pesantren. This study aims to uncover the spiritual chain (sanad) of the waẓīfa and to reveal why Ba‘alawi Sufi works are widely used at Pesantren Al-Fithrah. Using a qualitative approach, the data were collected from library research, field observations, and interviews. For analysis, it applies descriptive-analytical methods. The findings indicate that the practice of waẓīfa is rooted in Ba‘alawi Sufi traditions, due to some factors, including love (maḥabba) for Ba‘alawi as the descendants of Prophet Muhammad, Kiai Asrori’s lineage with Ba‘alawi Sufi figures, the connection of tariqa between Kiai Asrori and Ba‘alawi figures, and kinship ties between Kiai Asrori and Ba‘alawi Sufi figures. Contribution: This study contributes to revealing the waẓīfa sanad network of Pesantren Al-Fithrah Surabaya, which serves as a TQN al-Utsmaniyyah headquarters while adopting many spiritual practices, especially those derived from the works of Ba'alawi Sufi figures.